Validity and Reliability of Organizational Commitment using Confirmatory Factor Analysis (CFA) / Validitas dan Reliabilitas Komitmen Organisasi Menggunakan Confirmatory Analisis Faktor (CFA) - Sulistiawan, Agus; Diahsari, Erita Yuliasesti; Situmorang, Nina Zulida (Psikoislamika: Jurnal Psikologi Islam, 2020)
Turnover always occurs in companies, if it continues to increase, it will be detriment. Organizational commitment is a psychological state that characterizes the relationship between employee and organizations, in which the employee believes and wants to accept the goals and will remain or leave the organization as well as reflects the loyalty to a sustainable organization at which employees express their concern for the organization success and progress. The present study aims to evaluate validity and reliability score from measuring instruments based on the theory of Allen and Meyer. The dimensions that are used as reference for making the measuring instrument include affective commitment, continuance commitment, and normative commitment. This study was conducted on 92 nurses by using simple random sampling technique. The measuring instrument was made by scaling using a Likert model. The measurement of validity and reliability score used Confirmatory Factor Analysis (CFA) approach by PLS 3.3.2 software. The results showed that the organizational commitment measurement tool was declared valid and reliable as a measuring tool. There were 15 items dropped out of the 24 items tested.Keywords: Organizational Commitment; Validity; Reliability